The Fillmore Group Selects Attunity to Provide Real-time Data Integration Solutions to IBM Mainframe and DB2 Customers: Partnership to provide customers with affordable data integration solutions based on Attunity's technology and The Fillmore Group's IBM systems expertise (PR Newswire, 2011)
Statements preceded by, followed by, or that otherwise include the words "believes", "expects", "anticipates", "intends", "estimates", "plans", and similar expressions or future or conditional verbs such as "will", "should", "would", "may" and "could" are generally forward-looking in nature and not historical facts. Because such statements deal with future events, they are subject to various risks and uncertainties and actual results could differ materially from Attunity's current expectations.\n